Gender differentiation in risk-taking behavior: On the relative risk aversion of single men and single women - Oded Stark; Ewa Zawojska (University of Tübingen, Faculty of Economics and Social Sciences, 2015)
We relate an observed difference between single men (SM) and single women (SW) in attitudes towards risk to the higher value assigned to social status by SM than by SW. In the marriage market, low status carries a harsher penalty for SM than for SW because when selecting a partner, the social status of a man is more important to a woman than the social status of a woman is to a man. Correlating social status with relative wealth, we show how intensified distaste at experiencing low relative wealth reduces relative risk aversion.
urn:nbn:de:bsz:21-dspace-662855
Keywords: D03; D81; G11; G32; 330; Risk-taking behavior; Gender-based difference in risk aversion; Relative wealth deprivation; Social status; Marriage market outcome